ANALISIS KESIAPAN FASILITAS KESEHATAN DALAM PELAKSANAAN PROGRAM PEMERIKSAAN KESEHATAN GRATIS DI PUSKESMAS KEBUN KOPI - Annisa Dianty; Arnild Augina Mekarisce; Adila Solida (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the readiness of health facilities in implementing the Free Health Check Program (CKG) at Kebun Kopi Public Health Center using the Organizational Readiness for Change approach. The results indicate that the overall level of organizational readiness is moderate with a high level of vulnerability. Change commitment is very high due to compliance with government policies, but it is not matched by adequate change efficacy due to operational constraints. Human resource readiness reflects strong commitment but is challenged by workload overload and burnout risk. Infrastructure is sufficient in quantity but constrained by damaged equipment, limited reagents, and unstable digital systems. Budget limitations increase reliance on internal BLUD funds. Policies and SOPs are strong but lack flexibility. Socialization is extensive but hindered by low public trust in data security.